Pengembangan Jiwa Kepemimpinan Siswa di Masa Pandemi COVID-19 melalui Kegiatan Pramuka Berbasis Virtual: Developing Students’ Leadership Spirit during COVID-19 Pandemic through Virtual-Based Scouting Activities - Nunuy Nurmalia; Sri Nurhayati; Agus Hasbi Noor; Euis Eti Rohaeti; Enceng Mulyana (Society, 2022)
This research aims to analyze scouting activities’ implementation to improve students’ leadership qualities during the COVID-19 epidemic. This study used a descriptive method with a qualitative approach. The subject of this study consisted of 17 individuals: 1 school policymaker, 1 scout coach, and 15 scout members in Angkasa Lanud Husen Sastranegara High School, Bandung, Indonesia. Observation, interview and documentation study were data collection techniques used in this research. The findings of the study consisted of 1) scouting activities were included in the high school curriculum to prepare students to become individuals with good character and independence, have a spirit of leadership and concern for the environment, and equip students with positive activities before entering the community; 2) Virtual-based scouting education activities consisted of online scouting training with a leadership theme, to foster students’ leadership, scout members participated in virtual activities such as seminars, discussions, watching YouTube videos on the subject of scouting, and participating in Zoom Meeting on commemorating Scouting Day. The students attended Twigs and scout coaches’ training on scout groups throughout the pandemic. They also did the practice putting Tri Satya and Dhasa Dharma into practice in daily life. Students administered and applied the General Proficiency Requirements’ points. They played active roles in the quiz competition, which seeks to build a culture of sportsmanship and leadership, improving their capacity to communicate in a forum, acquire knowledge, assume responsibility, and gain experience. The scout members also practice developing a sense of leadership in their communities at home. They practiced serving as the prayer leader in the mosque, the imam of home prayers, and guided their younger ones to recite Quran. This research recommends that virtual-based scouting activities can be applied in all schools with more variations of programs and more appreciation for the students’ leadership improvement.